The Relationship between University Support and Students’ Digital Competence - Islamia, Intan; Arif, Andry Rahman (IJLHE: International Journal of Language, Humanities, and Education, 2024)
The advancement of technology in the 5.0 era necessitates that students develop strong digital literacy skills. This study examines the relationship between university support and students' digital literacy levels. Utilizing a quantitative research approach, data were collected from 99 respondents through two structured questionnaires: one measuring digital literacy and the other assessing university support. The data were analyzed using descriptive and correlational techniques with SPSS software. The findings reveal a significant positive correlation between university support and students' digital literacy. These results highlight that enhanced university support is associated with improved digital literacy skills among students. This study underscores the critical role of universities in delivering quality educational services that foster students' digital competence